Ribonucleases with Antiproliferative Properties: Molecular Biological and Biochemical Characteristics - VS Pokrovskii; EM Treshchalina; NV Andronova; SM Deev (Клиническая онкогематология)
The article dwells on ribonucleases (RNAses) whose cytotoxic activity depends on the enzymatic activity, i.e. the ability to catalyze the cleavage of phosphodiester bonds of RNA. It presents both well-known information and our own data on RNAses of different origins with antitumor properties; it investigates the relation between the mechanism of cytotoxicity and biochemical and molecular biological characteristics. The analysis of published data demonstrates that all above characteristics contribute to the antiproliferative activity of RNAses. The major challenge for this group of enzymes is the achieving of selective bioavailability. This problem can be solved by creating conjugates as in case with ranpirnase and barnase. Based on their major pharmacological properties, active antitumor RNAses have great perspectives for treatment of not only oncohematological, but also solid malignancies.